PENGARUH GENDER WANITA DALAM DEWAN DIREKSI TERHADAP KINERJA KEUANGAN STUDI PADA PERUSAHAAN YANG MASUK INDEX KOMPAS 100 TAHUN 2014-2015 - Muhammad Robi Nurwahyudi; Mudasetia Mudasetia (Sekolah Tinggi Ilmu Ekonomi Semarang, 2020)
Performance is a very important factor for the company. This study aims to test and empirically prove the effect of female gender on the Board of Directors on the financial performance of studies in companies included in the Kompass 100 index on the Indonesia Stock Exchange in 2014-2015. This research is a regrosi associative research. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange. The periodization of the study population was from 2014-2015. The sampling technique in this study used a purposive sampling method. The number of samples selected in this study were 83 companies. Data collection is done through documentation. The data analysis technique used is regression analysis. Testing is done through the help of the computer program Eviews version 9.0. Hypothesis testing is done through t test, F test, and determination test. The results showed that Gender had a significant effect on company performance. Tests prove that the research hypothesis is accepted, namely